Facile sonochemical synthesis and photocatalysis of Ag nanoparticle/ZnWO4-nanorod nanocomposites - Phattranit Dumrongrojthanath (2019)
© 2019, The Nonferrous Metals Society of China and Springer-Verlag GmbH Germany, part of Springer Nature. A facile sonochemical method was developed to synthesize metallic Ag spherical nanoparticles on the surface of ZnWO4 nanorods by forming heterostructure Ag/ZnWO4 nanocomposites. The Ag/ZnWO4 nanocomposites were characterized by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The experimental results showed that fcc metallic Ag nanoparticles were supported on surface of monoclinic sanmartinite ZnWO4 nanorods. The Ag 3d3/2 and Ag 3d5/2 peaks have well-separated binding energies of 6.00 eV, certifying the existence of metallic Ag. The Ag/ZnWO4 nanocomposites were evaluated for photodegradation of methylene blue (MB) induced by ultraviolet–visible (UV-Vis) radiation. In this research, heterostructure 10 wt% Ag nanoparticle/ZnWO4-nanorod composites have the highest photocatalytic activity of 99% degradation of MB within 60 min. The increase in photocatalytic activity was the result of photoinduced electrons in conduction band of ZnWO4 that effectively diffused to metallic Ag spherical nanoparticles and the inhibition of electron–hole recombination process.